Analisis Tentang Muatan Karakter Hindu Dalam Sistem Pendidikan Formal (Studi Pada Sekolah Menengah Atas di Kota Denpasar) - Hariadnya, I Gusti Ngurah Gede; Dantes, Nyoman; Wardhani, Ni Ketut Srie Kusuma (Jayapangus Press, 2019)
Character Education Strengthening is an educational movement under the responsibility of educational units to strengthen the character of students through harmonization of heart, taste, thought, and body with involvement and collaboration between educational units, families, and communities as part of the National Movement of Mental Revolution (GNRM). The importance of the Character Education Strengthening (PPK) policy, given that Indonesia is facing the 21st century marked by various global trends, namely the ongoing fourth industrial revolution, changes in civilization, the more stringent the phenomenon of the creative age.